AGRIMATION as Agribusiness Learning Media for Senior High School Students - Hidayat, Rohmat; Utami, Apriliyanti; Fatkhurozi, Anang (Program Studi Agribisnis, 2025)
The objective of this research is to develop ICT (Information and Communication Technology) based educational media in the field of agribusiness for use with high school students. Given the ongoing decline in student interest in the agricultural sector, this research aims to develop an attractive, informative, and technologically advanced media platform that will engage and educate young people about this important field. The methodology employed is that of research and development (R&D), utilizing the ADDIE model, which comprises five stages: The phases of the research process are as follows: analysis, design, development, implementation, and evaluation. Data were collected via questionnaires, expert validation, and trials involving students and teachers. The results demonstrated that the developed media exhibited a high degree of validity, with material validation scores reaching 91% and media validation reaching 88%. These findings indicate substantial approval from experts and users. The ICT-based media successfully incorporates interactive elements and multimedia content, thereby facilitating comprehension of agribusiness concepts and enhancing their appeal to students. The findings indicate that this media has the potential to serve as an effective instrument for fostering student interest in agribusiness and enhancing the quality of education in this domain. Further refinements are recommended to optimize the effectiveness of the media and enhance user engagement.